EXPECTATIONS FOR A POSITIVE INFLUENCE OF ARTIFICIAL INTELLIGENCE ON ARCHITECTURE IN THE NEAR FUTURE - Popov, Ivan (E-Journal VFU, 2025)
Artificial Intelligence (AI) is rapidly gaining popularity, and it is poised to transform the field of architecture. With AI, many of the tasks traditionally done by drafts-people can now be automated, including complex drawings and calculations. However, it’s crucial to use AI appropriately to maximize its benefits. While architecture has many different styles, there is currently a lot of overlap between them. Architects must constantly strive for innovation and unique projects, but not all attempts are successful. The effectiveness of AI in architecture ultimately depends on the expertise and skill of the professionals involved.